Impact of pleural reconstruction on postoperative outcomes in rib tumor resection: a decade-long retrospective study - Xie, Hao; Li, Bowen; Sun, Yixin; Ma, Lin; Zhang, Qiang (Frontiers in Surgery, 2024)
ObjectiveThis study aims to evaluate the effects of pleural reconstruction during rib compartment tumor resection surgery on postoperative outcomes, including drainage volume, drainage duration, hospital stay, complications, and pain control.MethodsA retrospective analysis was conducted on 142 patients who underwent rib compartment tumor resection surgery at Beijing Jishuitan Hospital from January 2013 to October 2023. The patients were divided into two groups: those who received pleural reconstruction and those who did not. Data were collected from hospital medical records and outpatient care records, focusing on postoperative drainage volume, total drainage time, length of hospital stay, complications, and pain scores. Continuous variables were compared using t-tests or nonparametric tests, while categorical variables were analyzed using chi-square tests or Fisher's exact tests.ResultsThe analysis showed no significant differences between the two groups in terms of postoperative complications and pain thresholds. However, patients who underwent pleural reconstruction had significantly lower postoperative drainage volume (937.74 ± 855.97 vs. 1,595.26 ± 1,054.50 ml, p < 0.05), shorter drainage duration (5.5 ± 2.39 vs. 8.43 ± 2.87 days, p < 0.05), and reduced length of hospital stay (7.32 ± 3.30 vs. 10.99 ± 6.83 days, p < 0.05).ConclusionPleural reconstruction during rib compartment tumor resection surgery reduces postoperative drainage volume, drainage duration, and hospital stay without increasing complications or short-term pain. Further large-scale studies are recommended to validate these findings.